The effect of material, thermal and laser conditioning on the damage threshold of type II tripler-cut DKDP crystals - Sun, Shao-Tao; Ji, Lai-Lin; Wang, Zheng-Ping; Xu, Ming-Xia; Liang, Xiao-Liang; Liu, Bing; Mu, Xiao-Ming; Sun, Xun; Xu, Xin-Guang (Crystal research and technology (1979), 2008)
By using the traditional temperature‐reduction method, KD2PO4 (DKDP) crystals were grown from 85%‐deuterated aqueous solution synthesized by different kind of KH2PO4 (KDP) raw materials. An experimental technique was employed to measure the variation of bulk damage threshold in plates of DKDP crystals. Bulk laser damage in unconditioned, thermal‐conditioned and laser‐conditioned type II tripler‐cut DKDP crystals has been studied using 1064 nm (ω) and 355 nm (3ω) laser at pulse lengths of 5ns, 5ns respectively. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)